A multinational observational investigation of illness perceptions and quality of life among patients with a Fontan circulation. (3rd January 2018) - Holbein, Christina E.; Fogleman, Nicholas D.; Hommel, Kevin; Apers, Silke; Rassart, Jessica; Moons, Philip; Luyckx, Koen; Sluman, Maayke A.; Enomoto, Junko; Johansson, Bengt; Yang, Hsiao‐Ling; Dellborg, Mikael; et al.
Abstract: Objective: First, to compare QOL and illness perceptions between patients with a Fontan circulation and patients with anatomically simple defects (ie, atrial septal defects [ASD] or ventricular septal defects [VSD]). Second, to explore illness perceptions as a mediator of the association between congenital heart disease (CHD) diagnosis and QOL. Design: Cross‐sectional observational study. Setting: Twenty‐four cardiology centers from 15 countries across five continents. Patients: Four hundred thirty‐five adult patients with congenital heart disease (177 Fontan and 258 ASD/VSD) ages 18‐83 years. Outcome Measures: QOL and illness perceptions were assessed by the Satisfaction With Life Scale and the Brief Illness Perceptions Questionnaire, respectively. Results: Patients with a Fontan circulation reported lower QOL (Wald Z = −3.59, p = <.001) and more negative perceptions of their CHD (Wald Z = −7.66, p < .001) compared with patients with ASD/VSD. After controlling for demographics, anxiety, depressive symptoms, and New York Heart Association functional class, path analyses revealed a significant mediation model, αβ = 0.15, p = .002, 95% CI = 0.06‐0.25, such that CHD diagnosis was indirectly related to QOL through illness perceptions. Conclusions: The Fontan sample's more negative perceptions of CHD were likely a reflection of life with a more complex defect. Illness perceptions appear to account for unique differences in QOL between groups of varying CHD complexity. Psychosocial screening and interventions may be important treatment components for patients with CHD, particularly those with Fontan circulations.